Working Element of a Horizontal Conveyor Type for Grass Raking - P. A. Eremin; V. V. Mikheev; A. Kh. Tekushev; M. Yu. Kostenko; V. P. Eremin (Сельскохозяйственные машины и технологии)
Horizontal conveyor working elements are used to increase productivity, reduce metal consumption and improve the quality of raking. This type of working element is promising for use in the design of hay-harvesting machines (rakes and roll doublers) and pick-up devices in balers. The authors have conducted research on the existing rake designs and using a 3D-model designed a working element of a horizontal conveyor type for cut grass raking.Research purpose Studying the rake design to obtain data on the design of the working element of a horizontal conveyor type for dried grass raking.Materials and methodsThe authors have used the analytical method and the 3D-modelling. The tasks of strength analysis were solved using standard finite element programs. The rake strength and durability were calculated. The working element design was implemented using the Solid Works CAD system using standard finite element programs.Results and discussion The authors have studied the main element of the original structure – the working element in the form of an endless narrow V-belt with its brackets housing spring-based rakes. They have also developed and offered a special device to prevent the belt from being dropped; analyzed the design and found a number of its significant shortcomings. The calculations have shown that the maximum stresses occur near the points of attachment and they are approximately equal to 545 MPa. The maximum elastic deformation of the rake is 2.1 millimeter. The authors have proposed a design scheme of fastening the rake on a wide belt, which eliminates the use of a device that prevents the belt from being dropped when the rake is colliding with an obstacle. Thus the raking body design has been greatly simplified. The proposed development will allow to reduce the rake weight by 0.6 kilograms and the total device weight by 14.4 kilograms.Conclusions The authors have obtained data sufficient to prove that the proposed design scheme would reduce the weight, energy consumption and production cost of the machine.